Intercultural perceptions and prospects of world Christianity - Friedli, Richard; Koschorke, Klaus (Studien zur interkulturellen Geschichte des Christentums, 2010)
Studies in the Intercultural History of Christianity, published by Peter Lang since 1975, is nowadays the largest series in the wide field of missiology, intercultural theology, and comparative religion/theology. The present editors decided to celebrate the publication of no less than one hundred and fifty volumes by evaluating and rethinking "intercultural theology". This book is meant to encourage Christian theology to be done more thoroughly, adequately, and effectively in the contemporary global and local setting. On the one hand, the volume offers new insights into the nature of doing biblical studies, church history, and systematic and practical theology as well as comparative theology, in an intercultural way. On the other hand, it argues for accomplishing interdisciplinary studies in the fields of theology and religion.